Atypical spindle cell/pleomorphic lipomatous tumor of the stomach: A case report - Raima Memon; Mohamed M. Abdelfatah; Chirag Patel; Deepti Dhall; Sameer Al Diffalha; J Bart Rose; Shi Wei; Goo Lee (Elsevier, 2021)
Atypical spindle cell/pleomorphic lipomatous tumor (ASPLT) is a newly accepted entity that belongs to the group of low-grade adipocytic neoplasms. ASPLT commonly manifests a soft tissue mass in both upper and lower extremities but is extremely rare in the gastrointestinal tract. Here we report a case of a gastric ASPLT in a 59-year-old male, who presented for the evaluation of new onset of dysphagia. To our best knowledge, this is the first case report of ASPLT in the upper gastrointestinal tract.